2003
DOI: 10.1096/fj.02-0699fje
|View full text |Cite
|
Sign up to set email alerts
|

The N‐ and C‐terminal fragments of ubiquitin are important for the antimicrobial activities

Abstract: Secretory granules of chromaffin cells contain catecholamines and several antimicrobial peptides derived from chromogranins and proenkephalin-A. These peptides are secreted in the extracellular medium following exocytosis. Here, we show that ubiquitin is stored in secretory chromaffin granules and released into the circulation upon stimulation of chromaffin cells. We also show that the C-terminal fragment (residues 65-76) of ubiquitin displays, at the micromolar range, a lytic antifungal activity. Using confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 84 publications
6
71
0
Order By: Relevance
“…2B) that exhibited differential activity against fungal and bacterial pathogens. We synthesized peptides corresponding to these sequences and found, consistent with the published data (28), that no activity was observed with Ub1, but Ub2 was capable of mediating significant antibacterial activity against both M. smegmatis and M. tuberculosis. Using a growth inhibition assay on M. tuberculosis, we determined that the Ub2 peptide exhibited an minimum inhibitory concentration of 5 M, indicating potent antimyco- bacterial activity that is consistent with the concentrations of ubiquitin found in the SFs (Fig.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…2B) that exhibited differential activity against fungal and bacterial pathogens. We synthesized peptides corresponding to these sequences and found, consistent with the published data (28), that no activity was observed with Ub1, but Ub2 was capable of mediating significant antibacterial activity against both M. smegmatis and M. tuberculosis. Using a growth inhibition assay on M. tuberculosis, we determined that the Ub2 peptide exhibited an minimum inhibitory concentration of 5 M, indicating potent antimyco- bacterial activity that is consistent with the concentrations of ubiquitin found in the SFs (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Previous work by Kieffer et al reported that peptides derived from ubiquitin were capable of microbicidal activity against a range of organisms (28). They identified two endoproteinasederived peptide sequences Ub1 and Ub2 (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…17 However, patients who were admitted to the emergency room after an accident but did not suffer from any injuries (ISS 0) did not show a significant increase in Ub serum concentrations, as compared with healthy volunteers. Thus, the contribution of Ub that is actively secreted during the stress response to its overall concentration in the systemic circulation after blunt trauma and burns is probably small.…”
Section: (Analysis Of Variance/tukey) (B-d) Same Patients As In (A)mentioning
confidence: 89%
“…13,14 Because other investigators provided evidence that it also regulates growth and apoptosis, and possesses antimicro-bial activity, [15][16][17] extracellular Ub may have pleiotropic effects on host defense mechanisms. Subsequently, we were able to confirm Ubs immune modulatory properties in vivo and showed that it has profound anti-inflammatory effects in various models of infectious and noninfectious inflammation.…”
mentioning
confidence: 99%